Ryż jako pokarm i medykament w antycznej i bizantyńskiej literaturze medycznej - Kokoszko, Maciej; Jagusiak, Krzysztof; Rzeźnicka, Zofia (Przegląd Nauk Historycznych, 2013)
The article discusses dietetic qualities of rice, its therapeutic applications and culinary recipes pertaining to the preparation of the cereal as described in ancient and Byzantine medical sources composed between I and VII c. AD (i.e. in the writings of Dioscurides, Galen, Oribasius, Anthimus, Alexander of Tralles, Aetius of Amida and Paul of Aegina). Although focused on the time span specified above, the authors of the study also make use of additional information present in the later literary medial tradition, composed as late as XI c. (up to the time of the compilation of Symeon Seths’s Syntagma de alimentorum facultatibus). The evidence also includes purely culinary sources, i.e. De re coquinaria attributed to Apicius. The article consists of three parts. The first chapter of the study is devoted to dietetic characterizations of rice and enlists features attributed to it over the ages. Accordingly, the authors maintain that the cereal is usually said to be hard to digest, not nourishing, astringent as well as slowing down the work of the alimentary tract (possibly leading even to constipation). The above-mentioned features were consistently made use of in ancient and Byzantine medical procedures. The second part of the study tries to retrieve from medical and culinary writings main culinary guidelines according to which rice was prepared as food. The authors conclude that, as a rule, the cereal was not used for bread baking, though it is likely that it was utilized in preparing cakes. Rice usually was the basis for preparation thick, gruel-like dishes which were normally compared to chondros or poltos, less thick soups which were said to be similar to ptisane, and watery, thin concoctions called chyloi, created by diluting rice stock. The cereal was usually cooked in meat stocks and sometimes in milk (the sources maintain that in this way rice improved the dietetic characteristic of milk by means of reducing its flatulence, preventing it from affecting the liver as well as counteracting stone formation in the bladder). The third chapter enumerates medical procedures which included rice and rice products. It is interesting that especially ample information on the subject comes from the VIth century, which could testify to a considerable popularity of rice in the field of medicine long before the time when it was finally introduced as a Mediterranean crop by the Arabs. Rice (due to its astringency) was mainly used to prepare enemas, which were in turn supposed to cure dysentery and other ailments resulting in excessive excretion of fluids of the body. It was also utilized to reduce swellings and cure gout, put and end to hemorrhages, and employed in medicaments removing unwanted hair and skin irritations. Last but not leas it was recommended in multiple diets usually prescribed by the doctors to those suffering from gastric problems.